The role of endoscopic ultrasonography (EUS) in contemporary diagnosis of gastrointestinal diseases - Kiełtucki, Jacek; Wawrzyniec, Katarzyna (Medical Studies/Studia Medyczne, 2016)
Day by day endoscopic ultrasonography (EUS) is becoming an essential diagnostic method for the assessment of solid lesions of the pancreas, cysts, pseudocysts and cystic tumours of the pancreas, enlarged mediastinal lymph nodes, staging of gastric cancer and rectal cancer, as well as lung or subepithelial tumours in the gastrointestinal tract. The ability to use this diagnostic method presents many challenges for performing specialists, from the organisation of the EUS surgery to maintaining its activity in a proper technical aspect, as well as the continuous improvement of staff qualifications. Endoscopic ultrasonography has revolutionised the practical aspects of gastroenterological practice and oncology. Particularly, EUS-guided fine-needle aspiration biopsy (EUS-FNA) of various pathologies in the gastrointestinal tract has provided invaluable effects and opportunities. This technique is becoming more and more available in Poland, creating a unique challenge to its practice.